2013
DOI: 10.5935/paet.v6.n1.07
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal activityin vitroandin vivoof neem oil onMeloidogyne incognita

Abstract: Considering the losses caused by nematodes in the different crops, chemical substances with nematicidal effect have been investigated and found in various plants. The neem oil is presented as an alternative to manage this pathogen. The aim of this study was to evaluate in vitro, the action of different doses of neem oil on the hatching and immobility of Meloidogyne incognita juveniles and in vivo in order to verify the data about the efficacy of neem oil to control nematodes of galls in tomato plants. In vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…From leaf-disc assays of neem oil on A. fragariae by An et al, demonstrated that neem oil caused 36.22% and 91.08% mortality in a 20 and 2-fold dilution (in 4.76% and 33.33% concentration, respectively) within 24 -72 hours of exposure time [15]. In a similar in vitro test on M. incognita J2, the use of neem oil in vitro was effective only in the immobility of M. incognita at concentrations of 1% in the control of active J2, with a percentage of 11% immobility that was different statistically from the control with 84.8% and smaller than the other treatments [8]. Neem oil is a type of vegetable oil that is made from the neem (Azadirachta indica) seed kernels.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…From leaf-disc assays of neem oil on A. fragariae by An et al, demonstrated that neem oil caused 36.22% and 91.08% mortality in a 20 and 2-fold dilution (in 4.76% and 33.33% concentration, respectively) within 24 -72 hours of exposure time [15]. In a similar in vitro test on M. incognita J2, the use of neem oil in vitro was effective only in the immobility of M. incognita at concentrations of 1% in the control of active J2, with a percentage of 11% immobility that was different statistically from the control with 84.8% and smaller than the other treatments [8]. Neem oil is a type of vegetable oil that is made from the neem (Azadirachta indica) seed kernels.…”
Section: Resultsmentioning
confidence: 88%
“…Most of the available investigations on neem oil, castor oil, and pyrethroids against nematodes were mostly targeted at root-knot nematodes Meloidogyne spp. [8,9,10] and a few studies on A. fragariae.…”
Section: Introductionmentioning
confidence: 99%